(24+32)x5+85-15=...
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)58(-45+-24)+-69.42
=58.(-69)+(-69).42
=-69.(58+42)
=-69.100
=-6900
a;
A= 58.(-45) + (-58).24 + (-69).42
A = -58.(45 + 24) - 69.42
A =-58.69 - 69.42
A = -69.(58 + 42)
A = -69.100
A = -6900
b; 139 - (-65 + 239) - (85 + 120)
B = 139 + 65 - 239 - 85 - 120
B = -(239 - 139) - (85 - 65) - 120
B = - 100 - 20 - 120
B = - 120 - 120
B = - 240
a) 460 + 85.4 = ( x + 200 ) : 4
=> x = 3000
b) => x = 2595
c) => x = 50
d) => x = 40
a)460 +85 . 4 = (x+200) :4 b)x:15+42=15+25.8
suy ra : 460+340=(x+200):4 suy ra: x:15+42=15+200
suy ra: 800= (x+200):4 suy ra : x:15+42=215
suy ra : 800.4=x+200 suy ra: x:15=215-42
suy ra : 3200=x+200 suy ra : x:15=173
suy ra: x= 3200-200 suy ra : x=173.15
suy ra : x=3000 vậy x =3000 suy ra: x=2595 vậy x = 2595
c) x-32:16=48 d)x-6:2-(48-24.2:6-3)=0
suy ra :x-2=48 suy ra : x-6:2-(48-48:6-3)=0
suy ra :x=48+2 suy ra : x-6:2-(48-8-3)=0
suy ra : x=50 suy ra : x-6:2-(40-3)=0
vậy x=50 suy ra : x-6:2 - 37=0
suy ra : x-3-37=0
suy ra : x-3=0+37
suy ra : x-3=37
suy ra : x=37+3
suy ra :x=40 vậy x= 40
a) \(4^8\cdot4^4=\left(2^2\right)^8\cdot\left(2^2\right)^4=2^{16}\cdot2^8=2^{16+8}=2^{24}\)
b) \(5^{12}\cdot7-5^{11}\cdot10\)
\(=5^{11}\cdot\left(5\cdot7-10\right)=5^{11}\cdot\left(35-10\right)=5^{11}\cdot25\)
\(=5^{11}\cdot5^2=5^{11+2}=5^{13}\)
d) \(27^{16}:9^{10}\)
\(=\left(3^3\right)^{16}:\left(3^2\right)^{10}=3^{48}:3^{20}=3^{48-20}=3^{28}\)
e) \(125^3:25^4=\left(5^3\right)^3:\left(5^2\right)^4=5^9:5^8=5^{9-8}=5\)
f) \(24^4:3^4-32^{12}:16^{12}\)
\(=\left(24:4\right)^4-\left(32:16\right)^{12}\)
\(=6^4-2^{12}\)
\(=2^4\cdot\left(3^4-2^8\right)=2^4\cdot-175=-2800\)
\(5^{12}.7-5^{11}.10\)
\(=5^{11}.\left(5.7-10\right)\)
\(=5^{11}.25\)
\(=5^{11}.5^2\)
\(=5^{13}\)
\(2^{20}.15+2^{20}.85\)
\(=2^{20}.5\left(3+17\right)\)
\(=2^{20}.100\)
\(=104857600\)
\(125^3:25^4\)
\(=\left(5^3\right)^3:\left(5^2\right)^4\)
\(=5^9:5^8\)
\(=5\)
\(24^4:3^4-32^{12}:16^{12}\)
\(=\left(24:3\right)^4-\left(32:16\right)^{12}\)
\(=8^4-2^{12}\)
\(=0\)
a, 460 + 85 . 4 = ( x + 200 ) : 4
460 + 340 = ( x + 200 ) : 4
( x + 200 ) : 4 = 800
x + 200 = 800 . 4 = 3200
x = 3200 - 200
x = 3000
=56x5+85-15
=280+85-15
=365 -15
=350